2020
DOI: 10.35975/apic.v23i4.1168
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and barriers pain management by nurses in Iran: A systematic review

Abstract: Introduction: Pain is a phenomenon that may be experience d every human being. Pain is one of the symptoms of the disease that has negative effects on patients and causes challenges in medical personnel. The aim of the present systematic review was to determine the knowledge, attitude, and pain management status in Iranian nurses. Methodology: This is a systematic review carried out according to systematic review articles checklist (PRISMA). The search was conducted by two researchers separately. In case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Systematic review studies provide comprehensive information (29,30) . This study is the first systematic review study to evaluate the Risk Factors of Elderly Falling in Public Hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review studies provide comprehensive information (29,30) . This study is the first systematic review study to evaluate the Risk Factors of Elderly Falling in Public Hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study conducted by Almomani et al (2021) in Jordan, the knowledge of ICU nurses about the use of physical restraint for patients was not at a desirable level (Almomani et al, 2021). Another study showed that ICU nurses' knowledge about endotracheal suctioning of intubated patients was limited (Mwakanyanga et al, 2018), and in Iran, a systematic review in 2019 showed that the level of knowledge of nurses in pain management was inadequate (Khalighi et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Pain is defined by the International Association for the Study of Pain as an unpleasant sensory and emotional experience related to or similar to that associated with actual or potential tissue damage (International Association for the Study of Pain, 2020). Pain is a symptom that has damaging effects on patients and brings about challenges to healthcare providers (Khalighi et al, 2019). Ung and colleagues (2016) have documented that the estimated incidence of moderate to severe pain is 20%–80% globally.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al (2012) have found that education program is effective in improving nurses' knowledge level and attitudes toward pain management. It is therefore essential to determine the level of nurses' knowledge, attitude, and barriers toward PAM to further improve pain management (Khalighi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%